Adaptive marketing capabilities, market orientation, and international performance: the moderation effect of competitive intensity - Reimann, Caroline Kalil (2022)
Purpose It is well established in marketing literature that international performance is positively affected by marketing capabilities, whether static or dynamic. However, recent theoretical development proposed adaptive marketing capabilities (AMC) as a set of capabilities able to close the marketing gap. Given the relative newness of this construct, empirical studies are still scarce. Therefore, drawing from a resource-based view perspective, this study aims to analyse the relationships among market orientation (MO), AMC and firms’ international performance, as well as the moderating effects of competitive intensity. Design/methodology/approach The authors have used survey-based research with 335 internationalised Portuguese business-to-business small and medium sized enterprises (B2B SMEs) during June 2020. The authors analysed responses through structural equation modelling and path analysis. Findings Results revealed positive relationships between AMC and international performance and between MO and AMC. Furthermore, results were robust to the competitive environment. Originality/value To the best of the authors’ knowledge, this study contributes to international marketing literature by analysing MO as an antecedent of AMC, which has never been done before. Furthermore, it analyses the simultaneous effects of MO and AMC on international performance, as well as the moderation of competitive intensity. Also, the study’s results inform managers and marketeers of internationalised firms about the advantages of adopting a market-oriented behaviour and the development of AMC, whether in more or less competitive environments.